Incidence of Neuropathy with Weekly Paclitaxel and Role of Oral Glutamine Supplementation for Prevention of Paclitaxel Induced Peripheral Neuropathy Randomized Controlled Trial - Abbas, Waseem; Rao, Ranga Raju; Agarwal, Amit; Saha, Rajat; Bajpai, Peush; Qureshi, Suhail; Mittal, Aditi (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Peripheral neuropathy is damage to the peripheral nerve. The most common cause of neuropathy is paclitaxel. Several avenues have been explored to ameliorate the neurotoxicity associated with paclitaxel. Clinical studies have assessed the efficacy of glutamine with different doses and schedules to prevent gastrointestinal toxicity (mucositis, diarrhea) and peripheral neuropathy in patients receiving a variety of chemotherapy agents or radiation therapy and found that glutamine can prevent paclitaxel-induced peripheral neuropathy. Methods: Total of 50 patients, aged 30 or more with diagnosis of cancer and fulfilling the inclusion and exclusion criteria, formed the study population. We assigned 25 patients to the glutamine group and 25 patients to no glutamine group. All patients received weekly paclitaxel. Results:: The incidence of neuropathy of all grades at 3 months was 78% and at 6 months was 80%.In this study, most common symptom reported was numbness in toes (74%). In this study, Grade 1 was the most common grade of symptom reported by the patient (40%–50%). 2nd, 3rd, and 4th most common grade of symptom reported by the patient was Grade 0, Grade 2, and Grade 3, respectively. There was no Grade 4 symptom reported by any patient. All the symptoms were statistically comparable in both groups (Myalgias: P = 0.066, Arthralgia: P = 0.93, Dysesthesia: P = 0.82, Paresthesia: P = 0.92, Numbness fingers: P = 0.97, Numbness toes: P = 0.60). In our study, there was no incidence of cranial nerve weakness or any incidence of the postural drop. The electrophysiological study is the best tool available and can detect neuropathy at the very earlier stage even when the clinical exam is negative. Apart from that nature of neuropathy can be determined but grading is not possible which makes very difficult to decide on follow-up examinations when the physician should intervene. Moreover, there are fluctuations in SNAP and CMAP, and these fluctuations are most probably related to the innate variability of serial nerve conduction study parameters, particularly motor and sensory amplitude. Glutamine did not prevent neurotoxicity induced by weekly paclitaxel.
Keywords: Glutamine supplementation for prevention of paclitaxel induced neuropathy; Incidence of neuropathy with weekly paclitaxel; Paclitaxel induced neuropathy